SOIL NUTRIENT STATUS ASSESSMENT OF SOME SOILS REPRESENTING THE GREEN BELT ZONE, SOUTH SUDAN - Thembinkosi, Tshabalala; Deng, Pio Kur; Marchelo-d’Ragga, Philip Wani (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Plant nutrients are chemical or organic elements necessary for plant growth often required in different amounts. Although they are taken in different quantities both micronutrients and macronutrients have the same agronomic importance and play various vital roles in plant growth. Soil testing is important and provide detailed information about nutrient variability such studies have not been conducted in the Green belt zone of South Sudan, thus the inception of this study; which would allow for the implementation of appropriate crop and soil management practices that align with the soil condition. Soil samples were collected and analyzed for pH, cation exchange capacity, organic matter, electrical conductivity, macronutrients, and micronutrients using standard procedures. The available Zn, Cu, Mn and Fe in soils was estimated using DTPA (Diethyl Triamine Penta Acetic Acid) which was found useful for separating soils into deficient and non deficient categories for Zn, Cu, Mn, and Fe by using atomic absorption spectrophotometer. Results indicated that the soils were generally, slightly acidic, slightly alkaline and alkaline (Mean = 7.03), low in CEC and medium in organic carbon, high in Ca K; and in Mg contents. The total Nitrogen and available Phosphorus at the study sites were low to medium in almost all soil samples. Also, Zn and Cu were also low to medium, respectively. Mn levels were also medium however Fe levels was below the critical limits for crop production. The study recommends supplementary application of nitrogen, phosphorus and micronutrient fertilizers for sustainable crop production in the studied soils and application of organic matter to improve the overall fertility of the soil.